Health literacy in relation to cancer: addressing the silence about and absence of cancer discussion among Aboriginal people, communities and health services. (21st May 2013) - Treloar, Carla; Gray, Rebecca; Brener, Loren; Jackson, Clair; Saunders, Veronica; Johnson, Priscilla; Harris, Magdalena; Butow, Phyllis; Newman, Christy
Abstract Cancer outcomes for Aboriginal Australians are poorer when compared with cancer outcomes for non‐Aboriginal Australians despite overall improvements in cancer outcomes. One concept used to examine inequities in health outcomes between groups is health literacy. Recent research and advocacy have pointed to the importance of increasing health literacy as it relates to cancer among Aboriginal people. This study examined individual, social and cultural aspects of health literacy relevant to cancer among Aboriginal patients, carers and their health workers in New South Wales. Qualitative interviews were conducted with 22 Aboriginal people who had been diagnosed with cancer, 18 people who were carers of Aboriginal people with cancer and 16 healthcare workers (eight Aboriginal and eight non‐Aboriginal health workers). Awareness, knowledge and experience of cancer were largely absent from people's lives and experiences until they were diagnosed, illustrating the need for cancer awareness raising among Aboriginal people, communities and services. Some beliefs about cancer (particularly equating cancer to death) differed from mainstream Western biomedical views of the body and cancer and this served to silence discussion on cancer. As such, these beliefs can be used to inform communication and help illuminate how beliefs can shape responses to cancer. Participants proposed some practical strategies that could work to fill absences in knowledge and build on beliefs about cancer. These results were characterised by a silence about cancer, an absence of discussions of cancer and an acknowledgement of an already full health agenda for Aboriginal communities. To promote health literacy in relation to cancer would require a multi‐layered programme of work involving grass‐roots community education, workers and Board members of Aboriginal community‐controlled health organisations and speciality cancer services, with a particular focus on programmes to bridge community‐based primary care and tertiary level cancer services.